Customer Evaluation of Supply Systems: The Case of Ethiopian Seed Supply Systems. Issue 4 (2nd October 2018) - Bogale, Shimelis Altaye; Verhees, Frans J. H. M.; Trijp, Hans C. M. van
ABSTRACT: This study explores the performance of Ethiopian seed systems from a customer's perspective. The study builds on the view that seed supply systems perform marketing functions such as developing new varieties of seed, multiplying the right quantity and quality, and distributing to the right places, at the right time, for an acceptable price. Hence, supply systems create value and satisfy customers. This study's contribution is twofold. First, customer satisfaction theory is applied to complex chains (i.e. seed supply systems) in emerging markets, with their specific contextual challenges. Second, it identifies the criteria that farmers use to evaluate seed supply systems and evaluates Ethiopian seed supply systems from a farmer customer's perspective, which can be used as a basis to increase customer satisfaction.